2021
DOI: 10.1038/s41467-021-24861-8
|View full text |Cite
|
Sign up to set email alerts
|

An umbrella review of the evidence associating diet and cancer risk at 11 anatomical sites

Abstract: There is evidence that diet and nutrition are modifiable risk factors for several cancers, but associations may be flawed due to inherent biases. Nutritional epidemiology studies have largely relied on a single assessment of diet using food frequency questionnaires. We conduct an umbrella review of meta-analyses of observational studies to evaluate the strength and validity of the evidence for the association between food/nutrient intake and risk of developing or dying from 11 primary cancers. It is estimated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(105 citation statements)
references
References 65 publications
0
77
0
5
Order By: Relevance
“…157,158 Recent extensive meta-analyses' have confirmed these trends and reported a strong association of colorectal cancer risk with dietary pattern and specifically with a low fiber, high fat and simple sugar containing diet. 159,160 Although there are several possible theories through which the anti-colon-cancer effect of the high fiber diet is thought to be mediated, the evidence from in-vitro studies have shown that butyrate plays a major role as an important intermediary metabolite in this pathway. 140,161,162 More research is needed to show the direct effects of gut microbially generated butyrate on anticolon cancer effects.…”
Section: Dovepressmentioning
confidence: 99%
“…157,158 Recent extensive meta-analyses' have confirmed these trends and reported a strong association of colorectal cancer risk with dietary pattern and specifically with a low fiber, high fat and simple sugar containing diet. 159,160 Although there are several possible theories through which the anti-colon-cancer effect of the high fiber diet is thought to be mediated, the evidence from in-vitro studies have shown that butyrate plays a major role as an important intermediary metabolite in this pathway. 140,161,162 More research is needed to show the direct effects of gut microbially generated butyrate on anticolon cancer effects.…”
Section: Dovepressmentioning
confidence: 99%
“…With regard to cancer incidence, a recent umbrella review concluded that there was sufficient evidence to conclude that several foods or nutrients were associated with cancer risk [6]. For instance, strong evidence was found for whole grains in relation to colorectal cancer risk.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, Papadimitriou and colleagues performed an umbrella review of evidence on the association of diet with the risk of 11 cancers (including RCC) [ 178 ]. The present study differs from their study in the following ways: (1) their literature was searched through March 2013, whereas ours was searched through April 2021; (2) the databases searched were not identical; (3) the present study included more recent meta-analyses and included more exposures (64 v 24), such as dietary inflammatory index, glycemic index, vitamin D, and riboflavin; (4) their study did not exclude overlapping SRoMAs and therefore, was likely to include duplicate individual studies, resulting in biased results and associations [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%